Characteristics of immune response profile in patients with immediate allergic and autoimmune urticarial reactions induced by SARS-CoV-2 vaccines - Wang, Chuang-Wei; Chen, Chun-Bing; Lu, Chun-Wei; Chen, Wei-Ti; Hui, Rosaline Chung-Yee; Chiu, Tsu-Man; Chi, Min-Hui; Lin, Jing-Chi; Huang, Yu-Huei; Chang, Ya-Ching; Wu, Jennifer; Chen, Kuan-Yu; et al. (Journal of autoimmunity, 2023)
Severe allergic reactions following SARS-COV-2 vaccination are generally rare, but the reactions are increasingly reported. Some patients may develop prolonged urticarial reactions following SARS-COV-2 vaccination. Herein, we investigated the risk factors and immune mechanisms for patients with SARS-COV-2 vaccines-induced immediate allergy and chronic urticaria (CU). We prospectively recruited and analyzed 129 patients with SARS-COV-2 vaccine–induced immediate allergic and urticarial reactions as well as 115 SARS-COV-2 vaccines–tolerant individuals from multiple medical centers during 2021–2022. The clinical manifestations included acute urticaria, anaphylaxis, and delayed to chronic urticaria developed after SARS-COV-2 vaccinations. The serum levels of histamine, IL-2, IL-4, IL-6, IL-8, IL-17 A, TARC, and PARC were significantly elevated in allergic patients comparing to tolerant subjects (P-values = 4.5 × 10−5–0.039). Ex vivo basophil revealed that basophils from allergic patients could be significantly activated by SARS-COV-2 vaccine excipients (polyethylene glycol 2000 and polysorbate 80) or spike protein (P-values from 3.5 × 10−4 to 0.043). Further BAT study stimulated by patients’ autoserum showed positive in 81.3% of patients with CU induced by SARS-COV-2 vaccination (P = 4.2 × 10−13), and the reactions could be attenuated by anti-IgE antibody. Autoantibodies screening also identified the significantly increased of IgE-anti–IL-24, IgG-anti–FcεRI, IgG-anti–thyroid peroxidase (TPO), and IgG-anti-thyroid–related proteins in SARS-COV-2 vaccines-induced CU patients comparing to SARS-COV-2 vaccines-tolerant controls (P-values = 4.6 × 10−10–0.048). Some patients with SARS-COV-2 vaccines-induced recalcitrant CU patients could be successfully treated with anti-IgE therapy. In conclusion, our results revealed that multiple vaccine components, inflammatory cytokines, and autoreactive IgG/IgE antibodies contribute to SARS-COV-2 vaccine–induced immediate allergic and autoimmune urticarial reactions. The immune mechanism of COVID-19 vaccines-induced immediate allergy and urticaria. A). The excipient or component of COVID-19 vaccines (such as PEG 2000, poly 80, tris, or spike protein) can be directly recognized by IgE antibodies, which coupled with their receptor-FcεRI on the mast cells or basophils, resulting in mast cell/basophil degranulation and triggering immediate allergic reactions. B). The excipient or component of COVID-19 vaccines can be recognized by B cells or presented to the T cells, resulting in autoreactive IgG/IgE antibodies production and increased cytokine/chemokine release. Moreover, IgG/IgE autoantibodies against self-antigens (e.g., IL24, TPO, etc.), may promote mast cell or basophil degranulation and cause delayed and chronic urticarial reactions. Abbreviation: IgE, immunoglobulin E; IL-24, Interleukin-24, PEG, polyethylene glycol; poly 80, polysorbate 80; TPO, thyroid peroxidase antibody, tris, tromethamine. [Display omitted] •Vaccine excipients as PEG 2000, polysorbate 80, tromethamine, and spike protein are identified as the culprit allergen(s) of SARS-COV-2 vaccines.•Multiple mast cell/T cell-mediated inflammatory cytokines and chemokines are involved in SARS-COV-2 vaccines-induced allergic reactions.•Autoreactive IgE/IgG antibodies (including IgE-anti-IL24, IgG-anti-TPO, IgG-anti-FcεRI, and IgG-anti-thyroid related proteins), contribute to SARS-COV-2 vaccines–induced autoimmune chronic urticaria.•Some patients with recalcitrant chronic urticaria following SARS-COV-2 vaccination can be successfully treated with anti-IgE therapy.